Drone-based SVP utilization for revitalizing under-valued public open spaces: Case of Istanbul - Lima Najjar; Fatma Aycim Turer Baskaya (Disegnare con)
Digital technology interventions become non-separable from contemporary urbanscape. This study discusses drone-based spatial video projection (D-SVP) as a digital alternative to revitalize under-valued public open spaces (UVPOSs). Spatial video projection is a projection-based augmented reality technology that enables the projection of visual content over 3-D objects of any scale. D-SVP is an integrated system suggested by this study where the drone will be supported by data collection and projection devices, which means that D-SVP works for both the data collection and showing at once. DOI: https://doi.org/10.20365/disegnarecon.29.2022.17